MCU meets cardiolipin: Calcium and disease follow form. (December 2020) - Yeung, Priscilla See-Wai; Prakriya, Murali
Abstract: Cardiolipin (CL) is a cone-shaped lipid found nearly exclusively in the inner mitochondrial membrane of animal cells. Disruption of CL synthesis leads to abnormalities in mitochondrial shape and function, but the underlying causes are incompletely understood. We highlight a new study that reveals that the activity of the mitochondrial calcium uniporter (MCU) is regulated by CL, advancing our understanding of the mechanisms of CL-linked human disease.